(untitled) (The International Journal for Scientific Research, 2023)
There is no doubt that foreign policy derives its foundations and dimensions from internal sources, and from that relationship foreign policy is affected by building the state internally, because the progress in the internal capabilities of the state and the development and advancement that it is witnessing through political engineering at home is capable of interacting in the regional framework through foreign policy so that these capabilities are A means of influencing the external framework (regional or international). When applying this to the case of Iraq, it is noted that the greatest threat to Iraqi foreign policy is an internal threat that comes in parallel with the threat from abroad, emanating from the state’s exposure to the risk of failure and collapse, as a result of deep political and societal divisions, weak governmental performance with repeated inability to build the state, so it had to be The study of Iraqi foreign policy begins with the study of the factors that help the state to restore the internal foundations of its strength.